CLASSIFICATION OF FIGURATIVE VERSES MISINTERPRETED BY CONTEMPORARY MOVEMENTS (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the dangers arising from the incorrect interpretationof figurative (mutashabih) verses in the Holy Qurʼan and their impact on Islamiccreed and society. The study analyzes how radical and deviant movements interpretQurʼanic expressions only in their literal sense while rejecting the traditional scholarlymethodologies of tafwid and taʼwil established by classical Sunni scholars. Specialattention is given to theological issues such as tajsim (anthropomorphism), tashbih(likening Allah to creation), and extremist literalism. Through the analysis of selectedQurʼanic verses including “The Hand of Allah is above their hands” (al-Fath, 10), “Allahplotted” (Al ʿImran, 54), and the dialogue between Musa (peace be upon him) and Allahregarding seeing Him (al-Aʼraf, 143) the article demonstrates how classical scholarssuch as Ibn Kathir, al-Baydawi, al-Nasafi, and Fakhr al-Din al-Razi interpreted theseverses within the framework of Arabic rhetoric, theology, and creed. The paper furtherdiscusses the misuse of figurative verses by extremist groups for political radicalizationand takfir. It concludes that preserving sound Islamic belief requires adherence to thebalanced methodologies of traditional Sunni scholarship, consideration of linguistic andhistorical contexts, and the strengthening of scholarly responses against superficial andextremist interpretations.
Keywords: Holy Qurʼan; mutashabih verses; figurative interpretation; taʼwil; tafwid; tajsim; tashbih; Islamic creed; radicalism; takfir; Qurʼanic exegesis; Arabic rhetoric; Sunni theology; Maturidism; Ashʿarism.